Capacity Building Workshop Report at the Kick-off meeting of the Pan-African Regional Programme - Hientz, Lennhart; Derenoncourt, Marie Ena (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Workshop report for the capacity building event where at the Kick-off meeting of the Pan-African Regional Green Climate Fund Readiness Programme on October 3-4, 2022 in Rabat Morocco. During the event, CGIAR scientists presented science-based tools such as the Adaptation Atlas and the Climate Smart Agriculture Investment Plan (CSAIP) methodology relevant for the GCF proposal to representatives from more than 30 African countries. This workshop created awareness about the portfolio of CGIAR research products that can enhance climate finance proposals for African countries.